Cost-benefit Analysis of Water Production with Seawater Reverse Osmosis System: A Case study for Mersin Free Zone and International Port - Sarica, Aytekin (International Journal of Economics and Financial Issues, 2018)
In this study, calculation of sea water reverse osmosis system cost has been used to determine local cost of the system and recycling time of investment. Local area owner and investor of the system are accepted as Mersin Free Zone and Mersin International Port due to common water usage areas, and real connection road is named as ‘’corridor’’. The local cost of the system was calculated as 0.49 /m 3 for 1000 m 3 /day capacity. Both companies take and use water which has a cost of approximately 0.75/m 3 from Mersin Metropolitan Municipality. The most important factors are determined as the sales volume and price of water for ships due to earnings from ships significantly decreased the recycling period of the system. The calculation of the system cost showed that the recycling time of the capital is less than 2 years, and after approximately 10 years, system which is assumed as 30 years lifetime would be completely free for the companies. Keywords: Reverse osmosis, water production, cost-benefit, economy JEL Classifications: D61, Q25